Children who screen positive for autism at 2.5 years and receive early intervention: a prospective naturalistic 2-year outcome study - Spjut Jansson B; Miniscalco C; Westerlund J; Kantzer A; Fernell E; Gillberg C (Neuropsychiatric Disease and Treatment, 2016)
Birgitta Spjut Jansson,1–3 Carmela Miniscalco,1,4 Joakim Westerlund,1,5 Anne-Katrin Kantzer,1,6 Elisabeth Fernell,1 Christopher Gillberg1 1Gillberg Neuropsychiatry Centre, Sahlgrenska Academy, Institute of Neuroscience and Physiology, University of Gothenburg, 2Unit of Child and Adolescent Habilitation, 3Department of Psychology, University of Gothenburg, 4Division of Speech and Language Pathology, Institute of Neuroscience and Physiology, University of Gothenburg, Gothenburg, 5Department of Psychology, University of Stockholm, Stockholm, 6Department of Child and Adolescent Psychiatry, NU Hospital Organization, Trollhättan, Sweden Background: Previous research has stressed the importance of early identification and intervention for children with autism spectrum disorders. Methods: Children who had screened positive for autism at the age of 2.5 years in a general population screening and then received a diagnosis of autism spectrum disorder were enrolled in an intervention program provided by Swedish habilitation services. The following interventions were available: a comprehensive intervention based on Applied Behavior Analysis – Intensive Learning (IL) – in two settings, which included home- and preschool-based (IL Regular) and only home-based (IL Modified) and eclectic interventions.Results: There was considerable variability in terms of outcome, but intervention group status was not associated with any of the chosen outcome variables. Conclusion: The main finding was that the type of intervention was not critical for outcome of adaptive or global functioning. The variability in outcome demonstrates the need for continuous assessments and evaluation of the child’s function and behavior throughout the intervention period. Keywords: autism spectrum disorder, preschool children, early intervention, ABA, cognitive function, follow-up